Sex Determination, Sex Differentiation and Puberty in Fish (Orinoquia, 2018)
In fish farming is useful to know the processes of sex determination and mechanisms that allow differentiation and the time in which maturation is reached and specimens are able to reproduce, these three processes are very flexible in specimens and not just rely different cascades of genes if some environmental factors are conditions or triggers them. So this review aims to take a look at the latest articles on the subject, scientific interpretations of the events of sexual maturation and their regulatory mechanisms, and review the management of his control.
Keywords: Reproduction; sex allocation; reproductive maturity; evolution; physiology